2013
DOI: 10.1016/j.bone.2012.09.037
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxygen during fracture healing

Abstract: Oxygen affects the activity of multiple skeletogenic cells and is involved in many processes that are important for fracture healing. However, the role of oxygen in fracture healing has not been fully studied. Here we systematically examine the effects of oxygen tension on fracture healing and test the ability of hyperoxia to rescue healing defects in a mouse model of ischemic fracture healing. Mice with tibia fracture were housed in custom-built gas chambers and groups breathed a constant atmosphere of 13% ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 49 publications
1
80
3
4
Order By: Relevance
“…In the context of bone repair, these investigators demonstrated that 10 days of hypoxia (FiO2 = 13%) slowed down bone formation and delayed callus remodeling in a mouse model of tibial closed transverse mid-diaphyseal fractures stabilized or not with external fixator. However, the onset of the hypoxic treatment likely accounts for the discrepancy between our data and the results presented by Makley et al [24] and Lu et al [25]. In both studies, mice were housed in the hypoxic chamber during the entire recovery period, namely, between the bone lesion surgery and the sacrifice times, whereas our hypoxic mice were housed for 7 days in normoxic conditions prior to being transferred into the hypoxic chamber for a 4-day period (sacrifice at postsurgery day 11).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In the context of bone repair, these investigators demonstrated that 10 days of hypoxia (FiO2 = 13%) slowed down bone formation and delayed callus remodeling in a mouse model of tibial closed transverse mid-diaphyseal fractures stabilized or not with external fixator. However, the onset of the hypoxic treatment likely accounts for the discrepancy between our data and the results presented by Makley et al [24] and Lu et al [25]. In both studies, mice were housed in the hypoxic chamber during the entire recovery period, namely, between the bone lesion surgery and the sacrifice times, whereas our hypoxic mice were housed for 7 days in normoxic conditions prior to being transferred into the hypoxic chamber for a 4-day period (sacrifice at postsurgery day 11).…”
Section: Discussioncontrasting
confidence: 56%
“…Contrary to our data, Makley et al [24] demonstrated in a rat model of fibula fracture subjected to chronic hypobaric hypoxia that the efficiency of bone repair is impaired. Such an observation was granted further support by a recent investigation [25]. In the context of bone repair, these investigators demonstrated that 10 days of hypoxia (FiO2 = 13%) slowed down bone formation and delayed callus remodeling in a mouse model of tibial closed transverse mid-diaphyseal fractures stabilized or not with external fixator.…”
Section: Discussionmentioning
confidence: 83%
“…The present study identified that CoCl 2 was able to significantly increase the expression of Runx2, ALP and OC. In spite of inadequate blood supply caused by hypoxia being a major cause of delayed union or non-union during fracture healing (24), an appropriate amount of hypoxia may aid in bone Figure 6. Schematic representation of the molecular mechanism of the effect of CoCl 2 on fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…for fracture healing, cells need oxygen (Lu et al, 2013a). In this study we have replaced the general oxygen decay term of the MOSAIC model with a cell-specific description of cellular oxygen consumption.…”
Section: Oxygen Consumptionmentioning
confidence: 99%